Chemical Constituents of the Leaf, Stem-bark and Root Essential oils of Antiaris africana - Moronkola D. Olufunke and Faruq U. Zaki (Journal of Applied Pharmaceutical Science, 2013)
Leaf, stem bark and root volatile oils were obtained from Antiaris africana Engl. a large attractive and medicinal deciduous timber tree (Moraceae) in 0.24%; 0.67% and 0.76% yields respectively. GC and GC-MS analyses revealed 10 compounds are responsible for leaf oil; 22 compounds make up 98.9% of the stem bark oil, while 6 compounds make-up 99.6% of root oil. 9 compounds were identified in leaf, which make-up 92.2% of it and 5 identified compounds in root represent 96.6% of it. Most abundant compounds in leaf oil are camphor (20.7%), 5-(1methylethylidene)-1,3-cyclopentadiene (16.8%), isomenthol (12.6%) and 1,3,5-trimethylbenzene (12.6%). Prominent compounds in stem bark oil are eucalyptol (19.3%), 4-methyl-1-(1methylethyl)-R-3cyclohexen-1-ol (17.4%), n-hexadecanoic acid (14.2%) and p-menth-1-en-8-ol (8.5%). Root oil is dominated by methylhexadecanoate (41.3%), 10-methyleicosane (30.4%) and methyl-13-octadecenoate (17.3%). Six other compounds in leaf oil, 18 others in stembark oil and 2 others in root oil along with above as reported are composition of Antiaris africana Engl. Leaf and stem bark oils are highly terpenic, having many interesting C10 and C15 terpenoids; Eucalyptus the most abundant compound in stem bark oil, is known to be medicinal; Presence of isomers of linalooloxide in stem bark oil is unique. Compositions of these three volatile oils are very interesting, which is scarce in literature.
Keywords: Antiaris africana, Moraceae, GC,